Leishmania infantum Lipophosphoglycan-Deficient Mutants: A Tool to Study Host Cell-Parasite Interplay - Lázaro-Souza, Milena; Matte, Christine; Lima, Jonilson B.; Arango Duque, Guillermo; Quintela-Carvalho, Graziele; de Carvalho Vivarini, Áislan; Moura-Pontes, Sara; Figueira, Cláudio P.; Jesus-Santos, Flávio H.; Gazos Lopes, Ulisses; Farias, Leonardo P.; Araújo-Santos, Théo; et al. (Frontiers in Microbiology, 2018)
Lipophosphoglycan (LPG) is the major surface glycoconjugate of metacyclic Leishmania promastigotes and is associated with virulence in various species of this parasite. Here, we generated a LPG-deficient mutant of Leishmania infantum, the foremost etiologic agent of visceral leishmaniasis in Brazil. The L. infantum LPG-deficient mutant (∆lpg1) was obtained by homologous recombination and complemented via episomal expression of LPG1 (∆lpg1 + LPG1). Deletion of LPG1 had no observable effect on parasite morphology or on the presence of subcellular organelles, such as lipid droplets. While both wild-type and add-back parasites reached late phase in axenic cultures, the growth of ∆lpg1 parasites was delayed. Additionally, the deletion of LPG1 impaired the outcome of infection in murine bone marrow-derived macrophages. Although no significant differences were observed in parasite load after 4 h of infection, survival of lpg1 parasites was significantly reduced at 72 h post-infection. Interestingly, L. infantum LPG-deficient mutants induced a strong NF-B-dependent activation of the inducible nitric oxide synthase (iNOS) promoter compared to wild type and ∆lpg1 + LPG1 parasites. In conclusion, the L. infantum ∆lpg1 mutant constitutes a powerful tool to investigate the role(s) played by LPG in host cell-parasite interactions.